E0615 The relationship between left ventricular diastolic function and arterial stiffness in coronary heart disease patients with diabetes. (17th November 2010) - Lian, Yankai; Wang, Yongliang; Li, Hongwei; Wu, Yongquan
Abstract : Objectives: By measuring left ventricular diastolic function and arterial stiffness, this study aims to probe into the effect of diabetes mellitus (DM) on left ventricular diastolic function and arterial stiffness, and evaluate the correlation between left ventricular diastolic function and arterial stiffness. Materials and methods: 76 inpatients who performed both coronary angiography and left ventricular angiography at the cardiovascular center of Beijing Friendship Hospital Affiliated with Capital Medical University from August 2009 to February 2010 were enrolled. Those with no diabetic history were given oral glucose tolerance test (OGTT). According to their coronary angiography, OGTT test results and past history of DM, patients were divided into controlled, CHD (Coronary Heart Disease) (with no DM), and CHD+DM groups. Through invasive haemodynamic monitoring during left ventricular angiography, left ventricular end-diastolic pressure (LVEDP) and tau index were collected. Carotid-femoral pulse wave velocity (c-f PWV), reflected wave augmentation index (AIx@75) and other data reflecting the degree of arterial stiffness were collected bedside with non-invasive means. SPSS 18.0 was used for statistical analysis. Results: (1) 37.5% (21 cases) of CHD patients were previous diagnosed type 2 diabetes before admission. Of those with no previous history of DM, 20% (7 cases) had impaired glucose regulation, and 28.6% (10 cases) were newly diagnosed type 2 diabetes. Overall, 67.9% (38 cases) of CHD patients also had abnormal glucose metabolism. (2) No significant differences were found between groups for left ventricular end diastolic pressure (LVEDP), tau index, and AIx@75. In terms of c-f PMV. The CHD+DM group (8.79±1.59 cm/s) differ significantly from the CHD group (7.43±1.42 cm/s) and the controlled group (6.83±1.14 cm/s). No correlations were found between c-f PMV and LVEDP or tau index. A positive correlation was found between AIx@75 and tau index. Conclusions: (1) Compared to the controlled group and CHD patients with no DM, CHD+DM patients showed worse arterial stiffness. No differences were found for left ventricular diastolic function. (2) There is a positive correlation between arterial stiffness and diastolic dysfunction.